Dusklands and the meaning of method. Issue 3 (15th April 2016) - Uhlmann, Anthony
Abstract : This essay develops a reading of J. M. Coetzee's first novel, Dusklands that considers questions of method. In the first instance, drawing on archival sources and secondary sources, it traces some elements of the methods used in the process of composition of the novel. It begins with Coetzee's interests in the work of Beckett and Nabokov, before turning to methods of juxtaposition developed in Dusklands . The nature of the relation between history and fiction and the nature of the relation between literature and politics and literature and its own form have provided much of the focus of the existing criticism of Dusklands . Connecting these problems is that of the relation between literature and its purpose: that is, the extent to which literature might be thought to enable an understanding or insight into what Coetzee has called the 'truth' that can inhere within fiction. From here the essay considers the question of method itself and how Coetzee's novel interrogates such methods, which determine what can and cannot be said about events, and what can and cannot be understood in relation to them.